Spur energy distributions in liquid water using a generalized oscillator strength from inelastic X-ray scattering measurements. (December 2017) - Karamitros, Mathieu; Mozumder, Asokendu
Abstract: The present paper utilizes the currently most accurate and complete generalized oscillator strength (GOS), determined experimentally using synchrotron X-rays, in constructing the spur energy distribution in liquid water. This replaces the earlier approximate evaluation using UV reflection and requiring long and uncertain extrapolation. Normalized distribution is provided as histograms of 5 eV bins up to 100 eV of energy loss for different incident electron energies. Certain other related quantities are also computed. These include the effective number of electrons receiving energy transfer, mean excitation potential and its effective value as a function of incident electron energy. This paper gives the results for first collision that is for the differential track, which is close to the integrated track result for high incident energy, as shown in some earlier calculations. On the whole, some earlier computations, but not all are approximately verified. Graphical abstract: Histogram of spur energy distribution in liquid water for incident electron of 10 keV energy. The first bin along the x-axis corresponds to an energy loss of 10 eV or less, then starting from the second bin, each bin corresponds to an interval of 5 eV of loss energy up to 100 eV such as: bin 2: (10–15 eV), bin 3: (15–20 eV), etc., bin 19: (95–100 eV). Highlights: Experimental generalized oscillator strength is used to compute inelastic cross-section. Energy loss distribution is calculated from the cross-section and shown as histograms. Comparison with early work using UV reflectivity shows significant differences. Energy-dependent mean excitation potential and electron number are recalculated.